Student Motivation to Learn Arabic in Sidoarjo Regency - Shinta Alkha Zhaqnixs; Imam Fauji (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to describe what motivates students to learn Arabic at Ma'had Umar Bin Al-Khattab Sidoarjo. This research is a qualitative descriptive study, the techniques used to collect data are direct and open observation techniques, unstructured interviews, and documentation. The results of this study indicate that most of the motives for learning Arabic for female students found an important point, namely that the motive for learning Arabic for female students of Ma'had Umar Bin Al-Khattab was the desire to learn religion. learn Arabic in various ways, namely: (a) In-depth understanding of what is said in prayer (b) Understanding what he reads from the verses of the Qur'an so that he can be guided by it and learn from it c) because of orders from people (d) the ability to study Islamic sciences from books written in Arabic, (e) because the place of study is not mixed with men (f) the ability to communicate with Muslims, because Arabic is the language of the nation Islam in this world.